Regulation of organic acid and hydrogen production by NADH/NAD+ ratio in Synechocystis sp. PCC 6803 - Akiyama, Minori; Osanai, Takashi (Frontiers in Microbiology, 2024)
Cyanobacteria serve as useful hosts in the production of substances to support a low-carbon society. Specifically, the unicellular cyanobacterium Synechocystis sp. PCC 6803 (Synechocystis 6803) can produce organic acids, such as acetate, lactate, and succinate, as well as hydrogen, under dark, anaerobic conditions. The efficient production of these compounds appears to be closely linked to the regulation of intracellular redox balance. Notably, alterations in intracellular redox balance have been believed to influence the production of organic acids and hydrogen. To achieve these alterations, genetic manipulations involved overexpressing malate dehydrogenase (MDH), knocking out D-lactate dehydrogenase (DDH), or knocking out acetate kinase (AK), which subsequently modified the quantities and ratios of organic acids and hydrogen under dark, anaerobic conditions. Furthermore, the mutants generated displayed changes in the oxidation of reducing powers and the nicotinamide adenine dinucleotide hydrogen (NADH)/NAD + ratio when compared to the parental wild-type strain. These findings strongly suggest that intracellular redox balance, especially the NADH/NAD + ratio, plays a pivotal role in the production of organic acids and hydrogen in Synechocystis 6803.